Operations and maintenance optimisation for a 100 MW wave energy farm in Ireland. Issue 3 (December 2022) - Giorgi, S.; Henry, A.; Kennedy, B.; Hoff, J. van ' t; Costello, R.; Lourdais, P.; Gaviglio, H.; Dickson, M.
No abstract available